2018
DOI: 10.31234/osf.io/ckdhz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling Atheist World Views in Different Cultural Contexts: Developmental Trajectories and Accounts

Abstract: In the current study, we look at atheist or secular identities in different religious landscapes: In the U.S., the majority of the population indicates a belief in God. In West Germany, one third of the population reports no religious affiliation and a quarter identifies as "not religious," and in East Germany, most of the population explicitly identifies as atheist. Drawing on atheist worldview and identity literature from multiple disciplines, and using quantitative and qualitative data obtained in the U.S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…More recent studies suggested that different degrees of atheism and agnosticism can be held and that these are consistently linked to various beliefs and attitudes (Schnell 2015 ). Furthermore, individuals who share the conviction that no god or higher power exists may still hold very different worldviews, as has been shown with regard to meaning in life (Schnell and Keenan 2011 ), spirituality (Schnell and Keenan 2013 ), and several other characteristics (Keller et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies suggested that different degrees of atheism and agnosticism can be held and that these are consistently linked to various beliefs and attitudes (Schnell 2015 ). Furthermore, individuals who share the conviction that no god or higher power exists may still hold very different worldviews, as has been shown with regard to meaning in life (Schnell and Keenan 2011 ), spirituality (Schnell and Keenan 2013 ), and several other characteristics (Keller et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though still in early stages, some scholars are now focusing on the substantive and positive beliefs of atheists and nonreligious people (as opposed only to what they do not believe) as they construct meaning around “big questions” by examining the social contexts in which they develop their views (Baker and Smith ; Lee ), the ways in which identity, disposition, and sets of beliefs across cultures become constitutive of worldview (Coleman, Hood, and Streib ; Keller et al. ), as well as the relationship of nontheism and nonreligion to other worldview systems including humanism, existentialism, and even analytic philosophy (see Bullivant and Ruse ). Research has already shown the centrality of science, critical thinking, and skepticism to atheists and other nonreligious individuals (Hunsberger and Altemeyer ; Smith ) and how their religious counterparts tend to have less confidence in science (Sherkat ).…”
Section: Empirical Research On Religion's Othermentioning
confidence: 99%